Differences between four skinfold calipers in the assessment of adipose tissue in young adult healthy population - Esparza-Ros, Francisco (2022)
Background: The aim of this study was to analyze the validity of four different skinfold calipers, as well as to establish the differences between them in a healthy young adult population. Methods: The present study followed a cross-sectional design, including 138 participants, with 69 males (21.46 ± 2.52 years) and 69 females (22.19 ± 2.85 years). The measurement protocol included basic measurements of body mass and stretch stature and eight skinfolds with a Harpenden, Holtain, Slim Guide, and Lipowise. The ∑6 and ∑8 skinfolds and fat mass were calculated. The order in which the skinfold calipers were used was randomized. Results: No significant differences were found in either the Σ6 and Σ8 skinfolds or masses and fat percentages calculated with the skinfolds obtained with the different calipers (p > 0.05), and the inclusion of the covariates of sex, BMI, and hydration status of the participants showed no effect on the differences. The Bland–Altman test showed significant differences between the calipers (p < 0.001). Conclusion: It has been observed that the analyzed calipers have shown validity for the assessment of adiposity-related variables in a male and female sample of non-overweight, young healthy adults, but they are not interchangeable with each other when the assessment is meant to be compared over time or with other samples.